A service-oriented approach for interactive computing systems (Publicaciones en Ciencias y Tecnología, 2011)
The introduction of new technologies leads to a more and more complex interactive systems design. In order to describe the future interactive system, the human computer interaction domain uses specific models, design processes and tools in order to represent, create, store and manipulate models. The aim of our work is to provide a theoretical conceptual approach to facilitate the work of model designers and project managers by helping them in choosing processes, models and modeling environments adapted to their specific needs. This paper details the use of a service-oriented approach for model management. Our proposals are related to three different abstract levels: the operational level to choose the appropriate modelling tool, the organisational level to select a design process and the intentional level to define modelling goals.
Keywords: HCI; model; service; model management; modeling tools; modeling services